Molecular transporter generation for quantum-molecular transmission via an optical transmission line - Jalil, Muhammad Arif (Elsevier B.V., 2010)
We propose a novel system of a quantum-molecular transportation using the multi-optical tweezers, whereby the transportation of molecules in the communication system can be performed. Initially, the generated transporter can be formed by a dark soliton. It can be tuned and attenuated to a single photon by bright soliton control and transmitted into an optical link. The molecule transportation states can be identified by using a single photon state of the transporter, which can be formed in the transmissionline. The proposed device can be fabricated using InGaAsP/InP, and can provide the required output signals. The design system consists of a nonlinear microring/nanoring resonator system incorporating an add/drop filter and a quantum signal processor. In applications, the proposed system incorporating a quantum processor can perform secure molecular communication as part of a molecular communication based data network.